SELF-IDENTITY IN A REPORT TO AN ACADEMY BY FRANZ KAFKA AND PISTOL PERDAMAIAN BY KUNTOWIJOYO - Sandra Dewi Dahlan (UIN Alauddin Makassar, 2020)
This research studied the concept of self-identity of the main character in A Report to an Academy and Pistol Perdamaian. This research also described the social relations between the main character and the otherness. The method used is qualitative and library research is the main technique of the research. The analysis is based on the theory of literary reception and the sociology of literature. The results showed that, in A Report to an Academy, the main character relies on the ratio to solve his problem, whereas, in Pistol Perdamaian, the ratio of the main character is defeated by the metaphysical irrationality associated with the belief system adopted. Thus, these two short stories also illustrated how the environment and the socio-cultural life influence the reaction of both main characters in understanding their existence among other beings.